2022
DOI: 10.3390/plants11131637
|View full text |Cite
|
Sign up to set email alerts
|

Computation Screening of Multi-Target Antidiabetic Properties of Phytochemicals in Common Edible Mediterranean Plants

Abstract: Diabetes mellitus is a metabolic disease and one of the leading causes of deaths worldwide. Numerous studies support that the Mediterranean diet has preventive and treatment effects on diabetes. These effects have been attributed to the special bioactive composition of Mediterranean foods. The objective of this work was to decipher the antidiabetic activity of Mediterranean edible plant materials using the DIA-DB inverse virtual screening web server. A literature review on the antidiabetic potential of Mediter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 157 publications
0
4
0
Order By: Relevance
“…The findings showed that green cumin positively and significantly impacted serum glucose levels and lipid profile [24]. Both cumin and NS oil help to control blood sugar by reducing the amount of TNF alpha, NF-kb, IL-1, and IL-6 and increasing the level of adiponectin.…”
Section: Introductionmentioning
confidence: 93%
“…The findings showed that green cumin positively and significantly impacted serum glucose levels and lipid profile [24]. Both cumin and NS oil help to control blood sugar by reducing the amount of TNF alpha, NF-kb, IL-1, and IL-6 and increasing the level of adiponectin.…”
Section: Introductionmentioning
confidence: 93%
“…Previous studies also support the antibacterial and carbohydrate digestive enzyme inhibitory potential of many phenolic compounds including phenolic acids, flavonoids, etc. [26][27][28]. Thus, the TPCs and TFCs of the native plants were first estimated.…”
Section: Total Phenolic Content (Tpc) and Total Flavonoid Content (Tf...mentioning
confidence: 99%
“…Daucus carota, Echium angustifolium, Prasium majus, and Smyrnium olusatrum also contain significant amounts of phenolic compounds. In the next step, the TFCs of native plants were assessed as flavonoids are a sub-group of phenolics with potent antibacterial and antidiabetic properties [28,30]. TFC values of plant extracts were strongly affected by extraction solvent and genetic factors; their contents fluctuated between 0.1 ± 0.0 mg catechin equivalents (CE) g −1 and 314.5 ± 23.0 mg CE g −1 (Figure 2).…”
Section: Total Phenolic Content (Tpc) and Total Flavonoid Content (Tf...mentioning
confidence: 99%
“…Authors founded that the flavonoids are the most active phytochemicals as they modulate the function of 17 protein targets and present a high structural similarity to antidiabetic drugs. Their antidiabetic effects are linked with three mechanisms of action, namely: (i) the regulation of insulin secretion/sensitivity, (ii) the regulation of glucose metabolism, and (iii) the regulation of lipid metabolism [ 16 ]. Molecular docking studies reveal that the Swingle can be a potential source of natural products due to its antibiotic-potentiating activity and since it is anti-SARS-CoV-2 [ 17 ].…”
mentioning
confidence: 99%